Knowledge of Rotavirus Gastroenteritis and its Current Preventive Strategies in Children, among Healthcare Providers in Ilorin, North-Central Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Rotavirus is a leading cause of severe gastroenteritis in children aged less than 5 years. Healthcare providers are responsible for implementing strategies for control of rotavirus gastroenteritis.Aims:To determine knowledge of healthcare providers regarding rotavirus gastroenteritis, its burden, management, and prevention.Materials and Methods:The study was a crosssectional descriptive survey of healthcare providers working in facilities caring for children. A selfadministered questionnaire was given to subjects containing questions on demographics and knowledge covering burden of rotavirus gastroenteritis, modes of transmission, age of occurrence, prevention, and rotavirus vaccines.Statistical analysis used:Data analysis was carried out with SPSS version 20.Results:Questionnaires were issued to 75 participants of which 65 (response rate = 86.7%) returned filled questionnaires. Majority (70.8%) of the subjects were females. Subjects included medical doctors (33.8%), nurses (32.3%), community health extension workers (27.7%), and laboratory scientists (4.6%). Most [39, 60.0%] subjects identified rotavirus as the commonest cause of diarrhea and only 21 (32.3%) indicated rotavirus contributed over 30% to the burden of diarrhea in these children. Fecooral route was recognized as a route of transmission by most subjects (95.4%) and 67.7% identified vaccination as a modality for prevention. Only six (9.2%) respondents could name any rotavirus vaccine. None of the demographic or occupational characteristics of the subjects was significantly related to awareness of effective rotavirus vaccines (all P > 0.05).Conclusions:Healthcare providers were aware of rotavirus as a cause of gastroenteritis in underfive children but most had poor understanding regarding its burden, prevention, and existing vaccines.